2020
DOI: 10.3390/antibiotics9120921
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cell Selectivity of Pseudin-2 via Substitution in the Leucine-Zipper Motif: In Vitro and In Vivo Antifungal Activity

Abstract: Several antimicrobial peptides (AMPs) have been discovered, developed, and purified from natural sources and peptide engineering; however, the clinical applications of these AMPs are limited owing to their lack of abundance and side effects related to cytotoxicity, immunogenicity, and hemolytic activity. Accordingly, to improve cell selectivity for pseudin-2, an AMP from Pseudis paradoxa skin, in mammalian cells and pathogenic fungi, the sequence of pseudin-2 was modified by alanine or lysine at each position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The mechanisms of action of numerous AMPs are broadly classified into the following two categories: membranolytic actions such as membrane potential changes and the formation of pores in the cell membrane; and intracellular inhibiting actions such as interfering gene expression, inhibiting enzyme activity, generating reactive oxygen species (ROS), and inducing osmotic pressure [ 28 , 29 ]. There is growing evidence of AMPs inducing cell death by stimulating the production of ROS [ 30 , 31 , 32 , 33 , 34 ]. Although fungal cells repeat the cycle of generating and eliminating intracellular ROS during metabolic pathways, the high levels of ROS damage intracellular lipids, proteins, DNA, organelles, and cell walls [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of action of numerous AMPs are broadly classified into the following two categories: membranolytic actions such as membrane potential changes and the formation of pores in the cell membrane; and intracellular inhibiting actions such as interfering gene expression, inhibiting enzyme activity, generating reactive oxygen species (ROS), and inducing osmotic pressure [ 28 , 29 ]. There is growing evidence of AMPs inducing cell death by stimulating the production of ROS [ 30 , 31 , 32 , 33 , 34 ]. Although fungal cells repeat the cycle of generating and eliminating intracellular ROS during metabolic pathways, the high levels of ROS damage intracellular lipids, proteins, DNA, organelles, and cell walls [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory concentration 50 (IC 50 ) against each fungus was defined as the lowest concentration of a sample that inhibited 50% visible growth. All assays were performed in triplicate [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Park and collaborators showed that the substitution of alanine or lysine within the leucine zipper motif in the pseudin-2 sequence suggested an increase in the selectivity of the microorganisms’ membranes ( Park et al, 2020 ). In addition, alanine-rich peptides are more likely to form a helix ( Zhuang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 0 and 100% releases were determined using only buffer (F0) and 0.03% ( w / v ) of Triton X-100 (Ft), respectively. The percentage of released calcein was calculated in the formula [ 44 , 45 , 46 ]: Release (%) = 100 × (F − F0)/(Ft − F0)…”
Section: Methodsmentioning
confidence: 99%